Nathan Carmody: capstone - Carmody, Nathan, artist (Colorado State University. Libraries, 2026)
The artist's statement: As a designer, I feel drawn to create works that are tactile, handcrafted, and approachable. One of the core tenants of design that resonates with me most is how design should be for everyone. Understanding that your creations will never be for you is one of the hardest parts of being a designer, but after embracing this truth, design becomes a bridge through which we as artists are able to build connections through intentional, human crafted experiences. Marrying a humanist approach to design, with my practice as a printmaker allows me to slow the practice of design down. In a culture that is driven by consumerism and instant gratification, honoring the texture, imperfection, and physicality of making becomes a way to reintroduce thoughtfulness into the process. My work aims to create moments of connection where people find meaning in the tangibility of the images they are seeing. They don't sit behind the gloss of a screen. They exist on the same level the viewer, occupying physical space in a way that encourages a more deliberate way of viewing.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design